2016
DOI: 10.1155/2016/9385027
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Absorption of Toluene from Exhaust Gas by Paraffin/Surfactant/Water Emulsion

Abstract: A new paraffin/surfactant/water emulsion (PSW) for volatile organic compounds (VOCs) controlling was prepared and its potential for VOCs removal was investigated. Results indicated that PSW-5 (5%, v/v) provided higher toluene absorption efficiency (90.77%) than the other absorbents used. The saturation pressure, Henry’s constant, and activity coefficient of toluene in PSW-5 were significantly lower than those in water, and toluene solubility (1.331 g·L−1) in the PSW-5 was more than 2.5 times higher than the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Hariz et al 14 studied the absorption process of toluene using vegetable oil−water as absorber. Fang et al 15 developed a new paraffin/ surfactant/water emulsion for controlling volatile organic compounds, and the results indicated that the paraffin/ surfactant/water emulsion has great prospect in organic waste gas treatment with the advantages of economy, high efficiency, and safety. Propylene carbonate 16,17 is a colorless, transparent liquid, which is an excellent organic solvent and intermediate for the synthesis of fine chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Hariz et al 14 studied the absorption process of toluene using vegetable oil−water as absorber. Fang et al 15 developed a new paraffin/ surfactant/water emulsion for controlling volatile organic compounds, and the results indicated that the paraffin/ surfactant/water emulsion has great prospect in organic waste gas treatment with the advantages of economy, high efficiency, and safety. Propylene carbonate 16,17 is a colorless, transparent liquid, which is an excellent organic solvent and intermediate for the synthesis of fine chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Various volatile organic compounds (VOCs) are produced in the petrochemical industry, including benzene, dichloromethane, acetone, and phenol [1,2]. To date, more and more attention has been paid to the treatment of dichloromethane and benzene because they are highly toxic, leading to the risk of human cancer [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…As the definition of VOC is somewhat extensive, VOCs encompass diverse classes of organic compounds such as alkanes, aromatics, aldehydes, ketones, alcohols and ethers, and the physicochemical properties of these compounds are all different (Fang, P. et al, 2016;Hodgson, M. et al,1994). However, a common characteristic of the VOCs is that the chemical group could be readily evaporated at room temperature.…”
Section: Properties Of Vocsmentioning
confidence: 99%